The Analysis of Electric Circuit Studio-based Virtual Laboratory for Dynamic Electrical Material - Budiarti, Indah Slamet; Logo, Novita; Gobay, Musa; Wombi, Nauli; Pamangin, Wilda Wijayani (Impulse: Journal of Research and Innovation in Physics Education, 2025)
This study aimed to analyze the use of a virtual laboratory based on an electric circuit (EC) studio on dynamic electrical materials and to help physics education students and to determine the effect of using an EC studio-based virtual laboratory on dynamic electrical materials. This study uses qualitative descriptive research with a survey method through the provision of questionnaires filled out by 15 second-semester students of the physics education study program, at Cenderawasih University. Quantitative data was collected using a questionnaire with an approach to science process skills on dynamic electrical materials with the help of the EC studio application, while qualitative data was in the form of responses given by students about virtual laboratory media on dynamic electrical materials. There are three indicators that serve as a reference in analyzing the EC studio-based virtual laboratory on dynamic electricity: learning motivation, the stimulus for higher-order thinking skills, and understanding of concepts and problem-solving. Based on the results of the questionnaire, it was found that students’ responses were very good to the EC studio-based virtual laboratory media because students could repeat themselves if they did not understand. The use of this media makes it easier for students to understand dynamic electricity.